COSMARIUM MANDOSII VAN WESTEN & COESEL 2020 (ZYGNEMATOPHYCEAE, STREPTOPHYTA), NEW SPECIES FOR UKRAINE, THE SECOND RECORD IN THE WORLD AFTER AUTHORS DESCRIPTION IN THE NETHERLANDS - Shyndanovina, Iryna (Biota. Human. Technology, 2025)
A new species of desmid algae - Cosmarium mandosii Van Westen & Coesel 2020, first described in the Netherlands in 2020, was discovered in the quarry pond “Zemsnariad” (Mlynovyshche Lake) in Chernihiv city (Ukraine). The aim of the study was to investigate the morphology of a representative of the species C. mandosii, discovered in the quarry pond (Chernihiv city), as well as to provide a taxonomic list of algae Zygnematophyceae, Streptophyta of the quarry pond “Zemsnariad”. Samples for algological analysis (periphyton of submerged parts and old leaves of Phragmites sp. and squeezed liquid Ceratophyllum demersum) were collected in June 2024 in the quarry pond “Zemsnariad”, which is located within Chernihiv city, close to its historical part. Both live samples and those fixed with 4 % formalin (for further storage and examination) were studied. Microscopic examination of the samples was carried out using light microscope Zeiss Imager A2 and Canon R6 camera. Some chemical parameters of the water were determined: 1) pH and electrical conductivity using portable multimeters H&M COM-100 and H&M PH-200; 2) the content of ions NO3-, SO42-, NH4+, Cu2+, Zn2+, Mn2+, Fetotal according to regulated methods in the local state laboratory of the Ministry of Health of Ukraine. It was established that the dimensional features of the representative of the species C. mandosii found in Chernihiv coincide with the data of other authors. This is the first published discovery of Cosmarium mandosii Van Westen & Coesel 2020 outside the Netherlands after the first description of this species in 2020. The algoflora of Ukraine is enriched with a new rare species. This is also the first published study of Zygnematophyceae, Streptophyta algae of the quarry pond ”Zemsnariad” (Chernihiv, Ukraine). C. mandosii was discovered together with 18 other taxa of desmid algae. The area of C. mandosii distribution in Europe was expanded. Illustrations of the Ukrainian material were provided. “Zemsnariad” quarry pond (Mlynovyshche Lake) is a locality of the new for Chernihiv Polesie species Cosmarium vexatum West 1892, and the new for Ukraine and rare for the world species C. mandosii.